2018
DOI: 10.1093/annonc/mdy425.002
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin-paclitaxel/nab-paclitaxel with or without pembrolizumab in first-line metastatic squamous NSCLC: Results from the KEYNOTE-407 east Asia subgroup

Abstract: Among 226 patients treated with icotinib, 71.7%(162/226) developed acquired resistance, and 28.3%(64/226) had primary resistance. Using the specimens at the baseline, there were 13(20.3%) patients with MET amplication, 8(12.5%) patients with BCL2L11 loss (BIM deletion polymorphism), 8(12.5%) patients with PTEN mutations, 6(9.4%) patients with MTOR mutations, 5(7.8%) patients with PIK3CA mutations, 3(4.7%) patients with FGFR3-TACC3 fusion, 2(3.1%) patients with EGFR T790M mutation, 2(3.1%) patients with HER2 am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…versus 45%, respectively), consistent with OS improvements observed in the all randomized population[29]. Subanalyses of the KEYNOTE-407 study in East Asian patients and the KEYNOTE-189 study in Japanese patients also favored first-line combination immunotherapy with pembrolizumab plus chemotherapy over chemotherapy in Asian/Japanese patients with metastatic squamous or nonsquamous NSCLC, respectively, consistent with findings in the all randomized population of each study[2,3,27,28].…”
supporting
confidence: 79%
See 2 more Smart Citations
“…versus 45%, respectively), consistent with OS improvements observed in the all randomized population[29]. Subanalyses of the KEYNOTE-407 study in East Asian patients and the KEYNOTE-189 study in Japanese patients also favored first-line combination immunotherapy with pembrolizumab plus chemotherapy over chemotherapy in Asian/Japanese patients with metastatic squamous or nonsquamous NSCLC, respectively, consistent with findings in the all randomized population of each study[2,3,27,28].…”
supporting
confidence: 79%
“…In a subanalysis of the phase 3 CheckMate 227 study in Asian patients with tumor PD-L1 expression ≥ 1% or < 1%, first-line treatment with nivolumab plus ipilimumab combination therapy demonstrated durable long-term survival and clinical benefits versus chemotherapy (median OS not reached versus 22.9 months; 2-year OS rate, 53% versus 45%, respectively), consistent with OS improvements observed in the all randomized population [ 29 ]. Subanalyses of the KEYNOTE-407 study in East Asian patients and the KEYNOTE-189 study in Japanese patients also favored first-line combination immunotherapy with pembrolizumab plus chemotherapy over chemotherapy in Asian/Japanese patients with metastatic squamous or nonsquamous NSCLC, respectively, consistent with findings in the all randomized population of each study [ 2 , 3 , 27 , 28 ]. On the other hand, in the IMpower132 trial, atezolizumab plus chemotherapy as first-line treatment for nonsquamous NSCLC showed apparent OS improvement versus chemotherapy in the Japanese subpopulation [median OS, 30.8 versus 22.2 months; HR 0.63 (95% CI 0.36–1.14)], but OS difference in the global population was not statistically significant between the treatment arms (median OS, 17.5 versus 13.6 months; p = 0.1546) [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…30,31 Subanalyses of the KEYNOTE-407 study in East Asian patients and the KEYNOTE-189 study in Japanese patients showed clinical benefits of first-line pembrolizumab plus chemotherapy over chemotherapy for metastatic squamous or nonsquamous NSCLC, respectively, consistent with results in the all randomized population of each study. 27,28,32,33 Similarly, in a subgroup analysis of the KEYNOTE-024 study in Japanese patients with metastatic NSCLC and PD-L1 tumor proportion score 50%, pembrolizumab monotherapy showed survival benefit over platinum-based chemotherapy, consistent with the outcomes for all randomized patients in the study. 34,35 Crossstudy comparisons should be made with caution, however, due to differences in patient populations, study design, and other key elements.…”
Section: Discussionmentioning
confidence: 61%
“…The consistent findings across subgroups and all randomized patients in this study are in line with prior studies that compared clinical outcomes of first-line immunotherapy for NSCLC between Asian and global populations. [27][28][29][30][31][32][33] In a subanalysis of Asian patients enrolled in CheckMate 9LA, first-line nivolumab plus ipilimumab in combination with two cycles of chemotherapy showed survival benefit over chemotherapy, consistent with results in all randomized patients. 30,31 Subanalyses of the KEYNOTE-407 study in East Asian patients and the KEYNOTE-189 study in Japanese patients showed clinical benefits of first-line pembrolizumab plus chemotherapy over chemotherapy for metastatic squamous or nonsquamous NSCLC, respectively, consistent with results in the all randomized population of each study.…”
Section: Discussionmentioning
confidence: 64%